Cell intrinsic control of axon regeneration - Mar, Fernando M (Blackwell Publishing Ltd, 2014)
Although neurons execute a cell intrinsic program of axonal growth during development, following the establishment of connections, the developmental growth capacity declines. Besides environmental challenges, this switch largely accounts for the failure of adult central nervous system (CNS) axons to regenerate. Here, we discuss the cell intrinsic control of axon regeneration, including not only the regulation of transcriptional and epigenetic mechanisms, but also the modulation of local protein translation, retrograde and anterograde axonal transport, and microtubule dynamics. We further explore the causes underlying the failure of CNS neurons to mount a vigorous regenerative response, and the paradigms demonstrating the activation of cell intrinsic axon growth programs. Finally, we present potential mechanisms to support axon regeneration, as these may represent future therapeutic approaches to promote recovery following CNS injury and disease.